TINDAK TUTUR LANGSUNG DAN TIDAK LANGSUNG GURU DALAM MATA PELAJARAN BAHASA INDONESIA DI KELAS XI SMA ADABIAH PADANG - Nurifa, Nurifa; Tressyalina, Tressyalina; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACT                 There are four research objectives. First, describing the forms of direct and indirect speech acts in terms of the types of illocutionary speech acts conducted by the teacher. Second, classifying the function of speech acts used by the teacher. Third, knowing the speech strategy used by the teacher. Fourth, find the context of the situation in the teacher's speech acts at XI grade students of SMA Adabiah Padang. The type of this research is qualitative research using descriptive methods. The data of this study are teacher's direct and indirect speech acts. This research instrument is the researcher himself. Data collection techniques are competent free participation techniques (SBLC), record, and note. Data validation techniques are triangulation techniques. There are five techniques used to analyze data.  There are four the results of this study. First, there are five forms of direct and indirect speech acts that are viewed from the types of illocutionary speech acts, namely assertive, directive, commissive, expressive, and declarative. Second, there are five functions of direct and indirect speech acts, namely: (1) assertive to state, notify, advise, boast, complain, demand, and report, (2) directive to order, order, request, request, advocate. Advising, (3) commissiveness to say (prayer), (4) expressive to say thank you, forgive, congratulate, and (5) declarative to drop the law. Third, there are two speech action strategies, namely positive politeness strategies and negative politeness strategies. Fourth, the context of using teacher-speaking strategies to students. Based on the results of the study, it can be concluded that the direct and indirect speech acts of the teacher have an effect on the Indonesian language subject while doing the teaching and learning process in the classroom.                                              Kata kunci: tindak tutur langsung dan tidak langsung, guru